Evolution of First Life without Oparin (Primordial Soup) Theory of Evolution: a Critical Review - Ahad, Md. Abdul (International Journal of Bio-resource and Stress Management, 2023)
Oparin theory (also known as Oparin- Handle theory) states that the first life was formed by a series of chance actions in the ocean and appears to have been the ancestor of the primitive cell- the first form of life. Currently this theory is known as the most modern and naturalistic theory about origin of the first life. Organic compounds are still present in huge amount in this planet, so life could be generated to it, and newer species of unicellular organisms could be produced frequently. But it is not happening at all. Modern cell theory, principle of biogenesis and Vitalism does not agree with Oparin theory at all. World renowned classical scientists such as Francesco Reddi, Antony Van Leauwenhok, Abbe Spallazani and Loius Pasteur were proved by different experiments that life does not come spontaneously from organic matter or any other sources, and a life only comes from a life. If Oparin theory be right then the classical experiments about the abiogenesis of the above scientists will be proved as wrong, as well as they become as nonscientist; but nobody will admit this. Recent theory of Nick lane (origin o of life at a special kind of deep-sea hydrothermal vent) and Helen Hansma (possible origin of life between mica sheets) opposed Oparin theory. Father’s of modern evolutionary theories such as Buffon, Lamarck and Darwin believed that life was first breathed by the Creator